Integration of human immunodeficiency virus type 1 DNA in vitro. - Farnet, C M (1990)
A highly efficient cell-free system for the integration of human immunodeficiency virus type 1 DNA is described. Linear viral DNA synthesis occurs in the cytoplasm of newly infected cells, reaching peak levels 4 hr after infection. The linear viral DNA molecules present in cytoplasmic extracts are capable of integrating into heterologous DNA targets in vitro. The viral DNA resides in a high molecular weight nucleoprotein structure that can be separated from the bulk of cellular protein and nucleic acid without a detectable decrease in the ability to integrate in vitro.